CFD analysis of hydrodynamic journal bearing with Bingham plastic lubricant considering roughness - Tauviqirrahman, Mohammad; Paryanto, P.; Pugastri, Ben Oni; Hamonangan, Andreas Partogi; Muchammad, M.; Yohana, Eflita; Jamari, J. (Cogent Engineering, 2023)
Utilizing a non-Newtonian lubricant, such as Bingham plastic fluid, in a hydrodynamic journal bearing affords the opportunity to actively alter the operating performance of the bearing. In this work, the main purpose is to explore the behavior of the journal bearing lubricated by Bingham plastic using the computational fluid dynamics (CFD) method considering roughness and cavitation. Here, the concept of an engineered partial roughness pattern is proposed to create positive effects in improving tribological and acoustic performances under different roughness levels and eccentricity ratios. The cavitation phenomena is modeled using the mixture multiphase cavitation approach to get a more realistic result. The numerical results of this study indicate that the surface roughness level of the roughed journal bearing has a significant effect on the load-carrying capacity irrespective of the eccentricity ratio. Moreover, the larger the roughness level, the lower the load-carrying capacity. It is also found that compared to bearings without roughness, it is possible to achieve a 5% and 2% reduction in noise level and friction force, respectively, when the "rough" level is employed on the roughed bearing. The findings of this research show that artificial partial roughness may be useful for enhancing journal bearing indices.
CRIS-Team WoS Importer:2023-06-02